2022
DOI: 10.3399/bjgpo.2021.0235
|View full text |Cite
|
Sign up to set email alerts
|

Communication skills of general practitioners in Nairobi, Kenya: a descriptive observational study

Abstract: BackgroundHigh quality primary care is associated with person-centeredness and effective communication that also supports continuity and coordination of care. In Kenya, there is little knowledge about the quality of communication in consultations by general practitioners (GPs).AimTo evaluate the quality of communication by GPs.Design & settingDescriptive, observational study of 23 GPs consultations in 13 private sector primary care facilities in Nairobi, Kenya.MethodOne consultation with a randomly selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It has also been shown to reduce the hyperutilization of primary care consultations 11 . We can therefore affirm that CS during the care interaction between doctor and patient are an essential tool 12 . These skills acquire special relevance when the patient suffers from SMI 13 .…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…It has also been shown to reduce the hyperutilization of primary care consultations 11 . We can therefore affirm that CS during the care interaction between doctor and patient are an essential tool 12 . These skills acquire special relevance when the patient suffers from SMI 13 .…”
Section: Introductionmentioning
confidence: 63%
“… 11 We can therefore affirm that communication skills during the care interaction between doctor and patient are an essential tool. 12 These skills acquire special relevance when the patient has an SMI. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Another manuscript that we reviewed having meet the requirement of an Effective Communication in the care of Patients with long term Disease in Kenya was a descriptive observational study (Mohamoud & Mash, 2022) [20] that evaluated the quality of communication in consultations by general practitioners (GPs) in Nairobi, Kenya. The study found that while GPs demonstrate skills in gathering information, making diagnoses, and suggesting management, there are areas for improvement in terms of patient-centered care and communication skills.…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…Though their weaknesses were that GPs did not make an appropriate introduction, explore the context or patients' perspectives, allow shared decision making, or provided adequate safety netting. Their consultations were brief and had a biomedical approach, lacking skills in whole-person medicine (Mohamoud & Mash, 2022) [20]. Furthermore, GPs lacked training in effective communication skills, particularly in delivering person-centred consultations and that the quality of communication was negatively impacted by the young and inexperienced GPs, who dealt with low-to-moderate complexity and mostly acute problems.…”
Section: Overview Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation